Hybrid Model to Measure QoE in IPTV: Methodological Proposal (PDF Download Available) (2015)
This article presents advances in research to obtain a hybrid model which allows the quality of experience within the residential IPTV service to be measured. The contents include a description of background information about objective and hybrid methods, the problem that needs to be resolved and the methodology to be used during the project. Our hybrid model will use quality of service parameters and a NR (No Reference) algorithm to evaluate the quality of video. This approach is not based on the results of subjective tests put forward to users previously. I. INTRODUCTION The current growth in IPTV service leads us to forecast that by 2016 this service will represent 88% of all global Internet traffic [1]. As a result, at some point in the future, this situation could lead to congested networks, degradation in the level of service provided, and therefore, end user dissatisfaction.